The STUDY OF CLOTHING REQUIREMENTS FOR CHILDREN WITH CEREBRAL PALSY: CLOTHING REQUIREMENTS FOR CHILDREN WITH CEREBRAL PALSY - Vahobova, Nargiza; Nigmatova , Fatima; Kozhabergenova , Kalamkul (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article highlights the results of research work in the field of designing clothes for disabled children with cerebral palsy. The requirements to clothing are developed, suitable types of clothing are determined, insufficient supply of adaptive products is revealed. On the basis of the obtained results of the work there is an opportunity to expand the assortment and design solutions of adaptive types of clothing with rehabilitation elements for this category of consumers.